Corporate social responsibility and food donation the case of food companies in Iloilo City (Iloilo City University of the Philippines Visayas, 2008)
The study focused on the characteristics, product lines, corporate social responsibility and food donation practices of food companies in Iloilo City. Characteristics included the company's vision statement, ownership structure, highest governing body and composition, capitaliztion, company size, nature of the company, gross monthly sales and target market. Product line referred to the types of food products, monthly production and distribution, monthly sales, product's life span, product's shelf life and reasons for product returns. Corporate social responsibility was seen in the policies and methods of disposal of returned food products looked into the company's ways of disposal of returned food products and reasons for food disposal.. significant considerations in formalizing linkages and consideratons in establishing the linkages. Food donation practices referred to the company's choice of organization as channel for food didtribution, organizational linkages, benefits from linkages, quantity of products donated, frequency of donation and type of organization most preferred as channel of food donation.
Research paper (M.M.) -- Iloilo City : U.P. Visayas, 2008.
Keywords: Social responsibility of business